practice-prelim-1 - Solutions to the practice prelim,...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
1. A) a) No . (1 + x ) d (ln( C + x )) dx = (1+ x ) ( C + x ) 6 = ln( C + x ) . b) Yes . (1 + x ) d (0) dx = 0 = 0 . c) Yes . (1 + x ) d ( C (1+ x )) dx = C (1 + x ) = C (1 + x ) B) i) Yes . x 2 d dx d ( x 2 ) dx = 2 x 2 = 2 x 2 ii) No . x 2 d dx d ( e x - 1 ) dx = x 2 e x - 1 6 = 2 e x - 1 2. A) dy dt = e t + y = e t e y . This is a separable equation, Z dy e y = Z e t dt + C. (1) We get from (1), - e y = e t + C . Using initial condition, we get C = - 2. Hence, our solution is, e y = - e t + 2 . (2) Taking logarithms, y ( t ) = ln(2 - e t ) . B) Clearly y ( t ) blows up if 2 - e t = 0, or t = ln2 which is finite. 3. Given equation, dy dt + y (1 + t ) = b. (3) Clearly, (3), is a linear differential equation and can be solved using integrating factor. ρ = e R 1 1+ t dt = e ln(1+ t ) = (1 + t ). Multiplying both sides of (3) by ρ , we get, d dt ± y (1 + t ) ² = b (1 + t ) . (4) Integrating (4), both sides with respect to t , we get, y (1 + t ) = bt + bt 2
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Image of page 2
This is the end of the preview. Sign up to access the rest of the document.

Page1 / 2

practice-prelim-1 - Solutions to the practice prelim,...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online